Systemic Treatment of Adrenocortical Carcinoma in Children: Data from the German GPOH-MET 97 Trial - Redlich, A.; Boxberger, N.; Strugala, D.; Frühwald, M. C.; Leuschner, I.; Kropf, S.; Bucsky, P.; Vorwerk, P. (Klinische Pädiatrie, 2012)
Adrenocortical cancer (ACC) in childhood is a rare disease with poor prognosis. Complete surgical resection, systemic chemotherapy, and mitotane therapy are important curative treatment options for patients with advanced-stage tumors. Since 1997, pediatric ACC patients in Germany have been treated according to the non-randomized, single arm study GPOH-MET-97.Data regarding disease course, treatment, and survival rates of 60 patients (age 0.24–17.8 years) with ACC treated according to the GPOH-MET-97 protocol were collected and analyzed to determine outcome, with a focus on examining the effectiveness of mitotane therapy.Among all patients, event-free survival and overall survival were found to be 43.3% and 64.8%, respectively. Chemotherapy with VCR, IFO, ADR, CARBO, and VP16 had been provided to 34 patients (56.6%) in different settings (neoadjuvant, adjuvant, and salvage) and mitotane therapy to 32 patients (53.3%). Duration of mitotane treatment longer than 6 months and mitotane levels greater than 14 mg/l were found to be associated with significantly better survival. Local relapse was found to be associated with a worse prognosis compared to distant metastasis only.Systemic chemotherapy and mitotane therapy are important therapeutic options in the treatment of advanced pediatric ACC patients. Neoadjuvant therapy should be considered for patients with primarily incomplete resectable or inoperable tumors, and tumor spillage is an indication for adjuvant chemo- and mitotane therapy. All pediatric ACC patients should be treated in pediatric oncological centers according to a consistent protocol in a highly interdisciplinary setting.
Keywords: adrenocortical carcinoma; GPOH-MET-97 protocol; mitotane; neoadjuvant therapy; pediatric oncology